Servant Leadership in Malaysian Da’wah NGOS: Western and Islamic Perspective - Mohd Faridh Hafez Mhd Omar; Sharifah Hayaati Syed Ismail (USIM Press, 2024)
Vol. 26 No. 1 (2022): Journal of Islamic Social Sciences and Humanities